2015
DOI: 10.1021/acs.jpcb.5b01904
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity Pattern of Bromonucleosides Induced by 2-Hydroxypropyl Radicals: Photochemical, Radiation Chemical, and Computational Studies

Abstract: The bromonucleosides (BrdX's) 5-bromo-2'-deoxyuridine (BrdU), 5-bromo-2'-deoxycytidine (BrdC), 8-bromo-2'-deoxyadenosine (BrdA), and 5-bromo-2'-deoxyguanosine (BrdG) may substitute for ordinary nucleosides in DNA. As indicated by electron-stimulated desorption experiments, such a modified biopolymer is greater than 2-3-fold more sensitive to damage induced by excess electrons. The other major product of water radiolysis, the (•)OH radical, may form a number of other radicals in chemical reactions with the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…This is why the reactivity of halogenated 2 0 -deoxynucleosides (brominated (BrdX) or iodinated (IdX)) toward organic radicals and solvated electrons (both types of species are produced during the radiolysis of cellular environment) was investigated in the current project. Using HPLC and LC-MS techniques, it was demonstrated that beside the substitution of bromine atom by 2-hydroxypropyl radical (OHisop ), electron transfer from OHisop to BrdX takes place only for 5-bromo-2 0 -deoxyuridine (BrdU) and 5-bromo-2 0 -deoxycytydine (BrdC) due to larger electron affinity (EA) of pyrimidines than purines [76]. The larger EA of brominated pyrimidines also accounts for more efficient damage induced by hydrated electrons in the trimeric oligonucleotides, TBrdXT, labeled with BrdU or BrdC [77].…”
Section: Working Group 2: Models Of Dna Damage and Consequencesmentioning
confidence: 99%
“…This is why the reactivity of halogenated 2 0 -deoxynucleosides (brominated (BrdX) or iodinated (IdX)) toward organic radicals and solvated electrons (both types of species are produced during the radiolysis of cellular environment) was investigated in the current project. Using HPLC and LC-MS techniques, it was demonstrated that beside the substitution of bromine atom by 2-hydroxypropyl radical (OHisop ), electron transfer from OHisop to BrdX takes place only for 5-bromo-2 0 -deoxyuridine (BrdU) and 5-bromo-2 0 -deoxycytydine (BrdC) due to larger electron affinity (EA) of pyrimidines than purines [76]. The larger EA of brominated pyrimidines also accounts for more efficient damage induced by hydrated electrons in the trimeric oligonucleotides, TBrdXT, labeled with BrdU or BrdC [77].…”
Section: Working Group 2: Models Of Dna Damage and Consequencesmentioning
confidence: 99%